The theses for MD degree - article Editorial (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
A.M. Polenov – Diagnostics and treatment of sphincter of Oddi dysfunction after cholecystectomy.S.A. Abdullayev – Clinical value of polymorphism of cytokine genes and hemochromatosis gene at chronic hepatitis C patients.S.A. Abdullayev – Clinical value of polymorphism of cytokine genes and hemochromatosis gene at chronic hepatitis C patients.